Effect of culture conditions on the content of B-phycoerythrins in Porphyridium cruentum cells - SUN Li-qin; WANG Chang-hai; TENG Li (浙江大学学报. 农业与生命科学版, 2007)
The variations in culture conditions determine different content of B-phycoerythrin (B-PE) from Porphyridium cruentum. In order to investigate the effect of culture conditions on B-PE synthesis, the cells of P. cruentum were cultured by different cultural parameters such as light quality, irradiance intensity, and nitrogen concentration, and then the B-PE was separated from soluble pigments of P. cruentum using the methods of deposited in 55% (W/V) solid ammonium sulfate and chromatographer on a hydroxylapatite column (HA). The results showed that the HA-column chromatographic method could purify the B-PE efficiently, and the purity of B-PE reached to 4.32 (OD545/OD280). The environmental factors could remarkably affect the B-PE contents in the P. cruentum cells. The green light could enhance the content of crude protein and B-PE compared with white light, and under appropriate conditions, both 24.56% crude protein and 9.14% B-PE were obtained respectively. In a defined range, the high light intensity was propitious to accumulation of B-PE in the cells, and with the increasing of light density, the dry weight of cell biomass and the content of proteins were also improved. At the same light intensity, the impact of nitrogen concentration on the yield of B-PE in the cells was notable. When the concentration of nitrogen was 3.20 g·L-1, both the growth rate of the cells and the content of B-PE arrive to their maximum value, and the content of B-PE accounted for 88.43% of total crude proteins in the cells.